Effects of partial substitution of grain by agroindustrial byproducts and sunflower seed supplementation in beef haylage-based finisher diets on growth, in vitro methane production and carcass and meat quality. (June 2022) - Santos-Silva, José; Francisco, Alexandra; Portugal, Ana Paula; Paulos, Kátia; Dentinho, Maria Teresa; Almeida, João M.; Regedor, Leandro; Fialho, Letícia; Cachucho, Liliana; Jerónimo, Eliana; Alves, Susana P.; Bessa, Rui J.B.
Abstract: Thirty-two bulls were assigned to four total mixed biodiverse haylage-based diets to evaluate the effects of partial substitution of grains by agroindustrial byproducts, sunflower seeds (SS) supplementation and haylage level on growth, in vitro methane production and carcass and meat quality. Dietary treatments included a grain-based diet with 30% grain and haylage:concentrate ratio (H:C) of 60:40 (DM basis) (MCe); a by-product-based diet where 50% of the grain was substituted for by-products (H:C, 60:40) (MBp); a byproducts diet with 10% sunflower seed and 90% (DM) MBp (H:C, 54:46) (MBpSS); and a byproducts, SS diet with increased haylage (H:C, 67.5:32.5) (HBpSS). Dry matter intake and growth rate were lower in HBpSS, but feed conversion ratio was unaffected by diet. In vitro methane emissions were reduced by SS. Meat colour and shear force were similar among diets. Lipid oxidation in cooked meat was reduced and fatty acid composition was improved with SS. Biodiverse haylage-based diets may be a viable option for finishing bulls. Highlights: Biodiverse haylage based-diets increased growth performance of bulls. Biodiverse haylage based-diets reduced the use of concentrates in finishing bulls. Inclusion of agroindustrial byproducts in bull diets had no impact on performance. The supplementation with sunflower seed reduced in vitro methane emissions. Supplementation with sunflower seed improved meat lipid composition and stability.